2013
DOI: 10.1039/c3ra40531a
|View full text |Cite
|
Sign up to set email alerts
|

Graphene oxide sheets as a template for dye assembly: graphene oxide sheets induce H-aggregates of pyronin (Y) dye

Abstract: The highly stable colloidal structure of graphene oxide (GO) in aqueous dispersion behaves as a platform for the molecular aggregation of dyes via a simple adsorption process. The interaction between dye and GO sheets is a critical factor for dye aggregation. Positively charged dyes interact with the negatively charged GO sheets in an aqueous dispersion via both electrostatic and p-p stacking interactions. The cationic nature of Pyronin Y (PyY) ensures that the dye molecules are quickly adsorbed on the GO shee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0
5

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 69 publications
(52 citation statements)
references
References 28 publications
0
46
0
5
Order By: Relevance
“…At dye concentrations lower than 1.5 µM, dye fl uorescence quenching was observed. [ 17 ] Since the fl uorescent dye concentration (6.25 mM) in this study was much higher than the reported threshold dye concentration (1.5 µM) and the GO sheet concentration (1 µg mL -1 ) used was much lower, quenching could have been negligible and thus fl uorescence was observed (Figure 3 B and Figure S1, Supporting Information). TEM images revealed GO sheet interaction with hASCs in the hybrid pellets (Figure 3 C).…”
Section: Go Incorporation Into Hasc Pelletsmentioning
confidence: 90%
“…At dye concentrations lower than 1.5 µM, dye fl uorescence quenching was observed. [ 17 ] Since the fl uorescent dye concentration (6.25 mM) in this study was much higher than the reported threshold dye concentration (1.5 µM) and the GO sheet concentration (1 µg mL -1 ) used was much lower, quenching could have been negligible and thus fl uorescence was observed (Figure 3 B and Figure S1, Supporting Information). TEM images revealed GO sheet interaction with hASCs in the hybrid pellets (Figure 3 C).…”
Section: Go Incorporation Into Hasc Pelletsmentioning
confidence: 90%
“…In general, H-aggregate structures are nonfluorescent and characterized with a red-shifted absorption band compared to that of monomeric species. In contrast, J-aggregates show a red-shifting and narrow absorption band compared to that of the monomer, and they are strong fluorescent species [2,4,8]. Chemically modified clays and clay minerals are an effective and popular class of adsorptive materials [9].…”
Section: Introductionmentioning
confidence: 91%
“…The figure showed that the absorbance of H-dimer in the bentonite suspension increased when the monomer absorbance decreased in the range of 0.1 to 10.0% CEC. This stemmed from the changing absorption characteristics of the dye due to the transition dipole-dipole interaction of dye monomers [2,4,8]. The fluorescence spectra of the dye in the natural bentonite aqueous suspension were shown in Fig.…”
Section: Absorption and Fluorescence Properties Of Mc-540 In Natural mentioning
confidence: 99%
See 1 more Smart Citation
“…It is reported that PyY can be exposed to molecular aggregation processes [13][14][15]. More recently, it is demonstrated that the photophysical properties of PyY can be affected by their interaction with other materials [16]. For example, graphene oxide, clays, polyelectrolytes and metallic NPs are commonly used changing the photophysical properties of dye molecules in M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 4 liquid media [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%